Music video (de)legitimacy and the construction of a (short form) auteur: David Fincher and talent management. Issue 2 (1st September 2021) - Stubbs, Andrew
This article explores David Fincher's collaboration with Propaganda Films, an integrated production and talent management company, during the late 1980s and early 1990s. Focusing specifically on Fincher's music video work, the article investigates how Propaganda's talent management strategies helped to develop Fincher's career and construct him as an auteur. To do so, the article adopts a cultural production approach conceptualizing the auteur as a branded identity and discourse mobilized in promotional and critical materials. In doing so, the article shows how Propaganda helped to single out Fincher's videos as artistic works showcasing the exceptional talent of an aspiring feature-filmmaker. At the same time, however, the article considers how Propaganda's talent management strategies contributed to sustaining problematic cultural notions surrounding music video and short-form work in general. As a result, the article advocates adopting new and more diverse approaches when examining short-form work and interrelated industry practice.